Smoking Prevalence, Patterns, and Cessation Among Adults in Hebei Province, Central China: Implications From China National Health Survey (CNHS) - He, Huijing; Pan, Li; Cui, Ze; Sun, Jixin; Yu, Chengdong; Cao, Yajing; Wang, Ye; Shan, Guangliang (Frontiers in Public Health, 2020)
As part of the China National Health Survey, this study aimed to explore the prevalence, patterns and influencing factors of smoking, and understand reasons for smoking cessation among adults in Hebei province, central China. Using a multistage stratified cluster sampling method, 6552 adults, 2594 males and 3958 females, aged 20-80 were selected in 2017. Demographic, socioeconomic and tobacco use information were collected by questionnaire interview. The prevalence of ever-smoking, current smoking and ex-smoking were 28.94%, 21.08% and 7.86%, respectively. Male participants had a much higher prevalence of ever smoking and current smoking (67.39% and 48.77%) than that of female (3.74% and 2.93%). In male participants, the daily cigarette consumption was 16.18, and the mean age of smoking initiation was 21.50, decreasing with birth year (27.50 in people who born before 1946 vs 17.9 after 1985, P for trend < 0.001). Over 80% of male ever smokers initiated regular smoking at the age of 15-29. Compared with never drinking, the ORs (95% CI) of low, moderate and high alcohol consumption were 1.44 (1.11-1.86), 2.80 (1.91-4.11) and 2.40 (1.72-3.33), respectively. Among 479 male ex-smokers, 50.94% stopped smoking because of illness and 49.06% by choice. Hypertensive men were more likely to quit smoking than the normotensive individuals (OR: 1.48, 95% CI: 1.13-1.96). For CVD patients, this effect was estimated as 2.27 (95% CI: 1.56-3.30). This study revealed a high prevalence of ever smoking, especially in men, in a representative population in central China. Health education focus on tobacco control could be integrated with alcohol consumption reduction to achieve additional benefit.